Root canal treatment in a dilacerated maxillary first molar: A case report - Mojtahed bidabadi, Maryam; Darmiani, Soheila (International Journal of Dental Research, 2014)
Aim: The aim of this clinical article is to describe the root canal treatment in dilacerated buccal roots that were detected in a maxillary first molar. Summary: Success in root canal treatment is achieved after thorough cleaning and shaping followed by the complete obturation of the root canal system. Such treatment may be performed in root canal systems that do not comply with the normal anatomical features described in standard textbooks. The present case describes root canal treatment in dilacerated buccal roots that were detected in a maxillary first molar.   Keywords: Dilacerations, root treatment, sever curvature.